Sistem Informasi Berbasis Website untuk Pengelolaan Data Program Kampung Iklim - Muhammad Zulkifli Mashar; Ningsi, Nurfitria; Pradipta, Anjar; Qammaddin, Qammaddin (Journal Research on Computing Knowledge, 2024)
Climate change is a worldwide concern that impacts several facets of existence, necessitating active community involvement in mitigation and adaptation initiatives. The Climate Village Program (Proklim), launched by the Ministry of Environment and Forestry, seeks to promote sustainable environmental management in communities. Nonetheless, the existing manual data management for Proklim frequently encounters obstacles including diminished productivity, insufficient transparency, and possible recording inaccuracies. This study seeks to create a web-based information system to facilitate Proklim data administration at the Kolaka District Environmental Office. The system employs the Model-View-Controller (MVC) architecture, utilizing the PHP programming language, Laravel framework, and MySQL database. Black Box testing findings demonstrate that the system can execute essential operations, such as user administration, data recording, and report production, with considerable accuracy. This system's installation improves the efficiency, accuracy, and transparency of Proklim data administration. This study enhances the utilization of information technology in environmental program management, specifically in promoting the sustainability of the Climate Village Program